2022
DOI: 10.1021/acsomega.2c00183
|View full text |Cite
|
Sign up to set email alerts
|

CuCo2S4@B,N-Doped Reduced Graphene Oxide Hybrid as a Bifunctional Electrocatalyst for Oxygen Reduction and Evolution Reactions

Abstract: In this report, a facile synthetic route is adopted for typically designing a hybrid electrocatalyst containing boron, nitrogen dual-doped reduced graphene oxide (B,N-rGO) and thiospinel CuCo 2 S 4 (CuCo 2 S 4 @B,N-rGO). The electrocatalytic activity of the hybrid catalyst is tested with respect to oxygen evolution (OER) and oxygen reduction (ORR) reactions in alkali. Physicochemical characterizations confirm the unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The concentration of the solution was 12 mg/mL, which was then air-dried overnight. This was followed by thermal reduction processes to obtain rGO free-standing layers [23]. This provides an eco-friendly and safer yet facile rGO synthesis and oxygen reduction route, which also enables mass production.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of the solution was 12 mg/mL, which was then air-dried overnight. This was followed by thermal reduction processes to obtain rGO free-standing layers [23]. This provides an eco-friendly and safer yet facile rGO synthesis and oxygen reduction route, which also enables mass production.…”
Section: Methodsmentioning
confidence: 99%
“…Another strategy for enhanced ORR activity was adopted by Roy Chowdhury et al , in which a hybrid catalyst was developed by employing CuCo 2 S 4 and dual heteroatom (B,N)-doped rGO. 171 The electrocatalytic investigations showed that the as-developed hybrid catalyst possessed enhanced bifunctional ORR and OER catalytic activity. In the case of the ORR, the as-synthesized CuCo 2 S 4 @B,N rGO exhibited significantly enhanced activity compared to CuCo 2 S 4 without B,N-doped rGO and Pt/C with a positive onset potential of 0.88 V, half-wave potential of 0.73 V and improved methanol tolerance.…”
Section: Advances In Orr Applications Of N-doped Graphene (Ng) Hetero...mentioning
confidence: 98%
“…34,35 The integration of electrocatalysts with a graphene oxide matrix often exhibits enhanced electrocatalytic activity due to a high surface area and good conductivity. 36,37 Heteroatom-doped graphene oxide nanocomposites showed strong electrocatalytic activity with excellent stability. 38,39 In particular, doping with highly electronegative F can modify the charge distribution of graphene and promote the adsorption process along with improving charge transfer and stabilizing 3d active metal centres.…”
Section: Introductionmentioning
confidence: 99%